(untitled) (Journal of Geography and Environmental Management, 2018)
2018 is significant with anniversary dates of Professor A.Т. Temirbekov. One of them is associated with his 75th anniversary. The labor, scientific and educational activities of the professor A.T. Temirbekov was addressed in the article.